Powerful unconfined turbidity current captured by cabled observatory on the Fraser River delta slope, British Columbia, Canada. Issue 5 (4th May 2016) - Lintern, D. Gwyn; Hill, Philip R.; Stacey, Cooper
Abstract: Turbidity currents are one of the main sediment transport processes on Earth, yet are notoriously difficult to monitor directly. This article presents the first direct and high bandwidth observation of a turbidity current using a cabled sea floor observatory. On 5 June 2012, a platform on Ocean Networks Canada, located in 107 m of water on the Fraser River delta slope, was displaced downslope and severed from its data cable. The platform weighed ca 1000 kg in water. The event took place during high river discharge, high tides and rapid sediment accumulation on adjacent upslope areas of the sea floor. Data recorded as it tumbled downslope allow a reconstruction of the flow, which is inferred to have been an unconfined turbidity current. Lines of evidence indicate that the flow came in as a bed hugging wedge, and built up to between 1 m and 4 m in height as the head passed through. Comparison with laboratory data suggest that the flow was initially supercritical. While the adjacent slope offset to the north clearly exhibits change over an annual resurvey period, the bathymetry directly at the event location show no resolvable change over a period from seven months before the event to one month after. Sediment cores collected after the event were pervasively biototurbated and they contain no obvious deposit connected with this event. The remarkable aspects of this research follow. The flow was powerful enough to carry a 1 tonne platform and sever a heavily armoured cable. The current occurred on the unchannelized open slope. This powerful event failed to cause discernible seabed elevation change. The flow was triggered by tidal conditions. The event was detected by a purpose‐designed cabled observatory, thus providing high bandwidth data and also alerting researchers in real time to mount follow‐on investigations.